2020
DOI: 10.3390/su12187657
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning for Conservation Planning in a Changing Climate

Abstract: Wildlife species’ habitats throughout North America are subject to direct and indirect consequences of climate change. Vulnerability assessments for the Intermountain West regard wildlife and vegetation and their disturbance as two key resource areas in terms of ecosystems when considering climate change issues. Despite the adaptability potential of certain wildlife, increased temperature estimates of 1.67–2 °C by 2050 increase the likelihood and severity of droughts, floods, heatwaves and wildfires in Utah. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Previous studies have shown that machine learning provides good species detection performance [73][74][75], and our study concurred that using machine learning approaches, notably thermal and RGB imageries, detected both Javan deer and water buffalo populations as experimental species. We found that water buffalo detectability performed better than for Javan deer.…”
Section: Species Diversity and Detection Techniques From Thermal Photographs Of Two Large-sized Mammals In Baluran National Park (Bnp)supporting
confidence: 88%
“…Previous studies have shown that machine learning provides good species detection performance [73][74][75], and our study concurred that using machine learning approaches, notably thermal and RGB imageries, detected both Javan deer and water buffalo populations as experimental species. We found that water buffalo detectability performed better than for Javan deer.…”
Section: Species Diversity and Detection Techniques From Thermal Photographs Of Two Large-sized Mammals In Baluran National Park (Bnp)supporting
confidence: 88%
“…For example, the models designed based on AI can serve as a tool for predicting the impacts of climate change on species distribution, abundance and interactions (Peterson 2001, Barlow and O'Neill 2020, Stupariu et al 2022). Additionally, AI can be employed for modeling the impact of human activities on ecosystem functioning, such as land‐use change (Carrero et al 2014, Wagner and de Vries 2019), pollution (Ye et al 2020, Masood and Ahmad 2021, Subramaniam et al 2022), or conservation planning (Mosebo Fernandes et al 2020). For example, AI algorithms could be used to predict the effects of land‐use change on biodiversity or to identify areas that are most at risk of pollution (Mosebo Fernandes et al 2020, Ye et al 2020).…”
Section: Exploring the Role Of Ai In Ecology: Improved Chatgpt Perspe...mentioning
confidence: 99%
“…ANNs are analogous to the organic nervous system in that they use numerous hidden layers to anticipate LULC. 33,34 The input, hidden, and output layers make up a neural network, a computational model made up of significant nodes. 35 The output layer of a previous node could become the input layer of the following node in this method, and the network's output changes depending on linking styles, weight values, and incentive functions.…”
Section: Lulc Classificationmentioning
confidence: 99%